Iron-promoted free radical cascade difunctionalization of unsaturated benzamides with silanes. Issue 83 (23rd September 2020) - Ge, Yaxin; Tian, Yunfei; Wu, Jilai; Yan, Qinqin; Zheng, Luping; Ren, Yingming; Zhao, Jincan; Li, Zejiang
Abstract : An efficient cascade difunctionalization of unsaturated benzamides with silanes was developed for the synthesis of various silylated dihydroisoquinolinones and 1, 3-isoquinolinediones. Abstract : Iron salt/peroxide promoted cascade difunctionalization of unsaturated benzamides with silanes has been reported. It provides a convenient, highly selective, and efficient protocol for the synthesis of various silylated dihydroisoquinolinones and 1, 3-isoquinolinediones. In particular, the present methodology only gives cyclization products in good isolated yields under the typical conditions.